2022
DOI: 10.1108/jieb-06-2021-0068
|View full text |Cite
|
Sign up to set email alerts
|

Integrating financial literacy into economics courses through digital tools: the Finlite app

Abstract: Purpose This study aims to analyze the effect of the Finlite mobile app on the financial literacy of undergraduate business students in Malaysia. Design/methodology/approach This study uses a quasi-experimental pre-intervention design. The data are collected using a quiz and a questionnaire. Cluster sampling is adopted for three different zones in Malaysia. A total of 400 business students enrolled in economics courses participated in the intervention. Findings The results indicate that Finlite significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Graphical representations, such as online financial calculators with graphing capabilities, can serve to support student learning by removing the computational effort and allowing students to process concepts aiding in decision making (Puntambekar and Hubscher, 2005). Other studies have shown videos (Kuntze et al, 2019;Lusardi et al, 2017), digital tools (Yin et al, 2022), web research exercises and budget applications (Angel, 2018) as particularly effective in supporting financial literacy education. Use of digital and virtual tools are recommended to complement rather than substitute in-person classes or workshops (Abt Associates, 2021;Angel, 2018).…”
Section: Recommendations Regarding Financial Literacy Educationmentioning
confidence: 99%
“…Graphical representations, such as online financial calculators with graphing capabilities, can serve to support student learning by removing the computational effort and allowing students to process concepts aiding in decision making (Puntambekar and Hubscher, 2005). Other studies have shown videos (Kuntze et al, 2019;Lusardi et al, 2017), digital tools (Yin et al, 2022), web research exercises and budget applications (Angel, 2018) as particularly effective in supporting financial literacy education. Use of digital and virtual tools are recommended to complement rather than substitute in-person classes or workshops (Abt Associates, 2021;Angel, 2018).…”
Section: Recommendations Regarding Financial Literacy Educationmentioning
confidence: 99%
“…Additionally, the questionnaires were developed on the basis of the TPB and values in financial literacy. There were five key areas in the questionnaires [55], namely practices, decision making, accountability, ability to overcome obstacles and human values. Example of an item, "I have a saving account."…”
Section: Instrumentsmentioning
confidence: 99%
“…Understanding the impact of race on SDL can provide valuable insights into designing effective educational interventions that cater to the diverse needs of students from different racial backgrounds. One study byYin et al (2022) highlights the importance of considering different races in Malaysia and the study suggests that different races in Malaysia have different behaviors and attitudes. This finding emphasizes the need for SDL study on the culture and race in the country.…”
mentioning
confidence: 99%